PSYCHODIAGNOSTIC POSSIBILITIES OF IMPLEMENTING PSYCHOLOGICAL SERVICES IN GENERAL SECONDARY SCHOOLS - Omonova S. M. (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to the topic of psycho-diagnostic possibilities of providing psychological services in general secondary schools. Also, in the text of the article, the psycho-diagnostic activity of a practical psychologist, psycho-diagnostic work and its content, the basics of psychological diagnosis, psycho-diagnostic work at school, psychological selection, professional guidance, research of children's special abilities, general knowledge tests, psychological assessment, gifted students, etc. analyzed.